Investing in climate-resilient agriculture in Zambia’s rural communities: challenges, opportunities, and pathways for scaling - Jalango, Dorcas Anyango; Nzuki, Esther Ndumi; Banda, Emely Mwale (2025)
This report documents Zambia’s experience in advancing climate-resilient agriculture through the Strengthening Climate Resilience of Agricultural Livelihoods in Agro-Ecological Regions I and II (SCRALA) project and its complementarity with the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) initiative. It highlights communitydriven models that integrate Climate-Smart Agriculture (CSA), financial inclusion, and market access to build resilience and enterprise capacity among smallholder farmers. Field evidence from Kazungula District demonstrates how farmer field schools, cooperatives, and savings groups are transforming adaptation practices into investable opportunities. The report identifies key lessons, financing gaps, and strategic pathways for scaling inclusive, climate-smart agricultural investments.